Survei Diare pada Siswa Sekolah Dasar di Wilayah Singkawang Selatan - Ade Maiditasari; Ruqiah Ganda Putri Panjaitan; Yokhebed Yokhebed (Jurnal Vokasi Kesehatan, 2019)
Abstract: The Relationship Between Healthy Life Behavior With Diarrhea Events. One of the causes of diarrhea is low healthy living behavior. This study aims to determine the causes and eï¬€orts to control diarrhea in children in the District of South Singkawang. This type of research is qualitative descriptive survey methods and techniques of data collection using interviews and questionnaires. The sampling technique with a purposive ie 60 students from three primary schools and six medical personnel from three health centers in the district of South Singkawang. The survey results show the cause of diarrhea in primary school students in the District Singkawang South are still many students who do not wash their hands with soap after defecation and activity, eating snacks are not healthy, the use of the toilet and polluted water, as well as the habit of throwing rubbish indiscriminately. Prevention eï¬€orts may include maintaining the cleanliness of individuals and families, especially the cleanliness of food and beverages as well as the neighborhood. It can be concluded that the cause of diarrheal disease in primary school students because of a lack of awareness of clean and healthy. Furthermore, the need for greater eï¬€orts to sensitize students about clean and healthy lifestyle. Â Abstrak: Survei Diare pada Siswa Sekolah Dasar di Wilayah Singkawang Selatan. Salah satu penyebab diare adalah perilaku hidup sehat yang rendah. Penelitian ini bertujuan untuk mengetahui penyebab dan upaya penanggulangan diare pada anak di Kecamatan Singkawang Selatan. Jenis penelitian ini adalah kualitatif dengan metode survei deskriptif serta teknik pengumpulan data dengan menggunakan wawancara dan penyebaran angket. Teknik pengambilan sampel dengan cara purposive yakni 60 siswa dari 3 sekolah dasar dan 6 orang tenaga medis dari 3 Puskesmas di Kecamatan Singkawang Selatan. Hasil survei menunjukkan penyebab diare pada siswa sekolah dasar di Kecamatan Singkawang Selatan adalah masih banyaknya siswa yang tidak mencuci tangan dengan menggunakan sabun setelah buang air besar dan beraktivitas, mengonsumsi jajanan yang tidak sehat, penggunaan jamban dan air yang kotor, serta kebiasaan membuang sampah secara sembarangan. Upaya penanggulangan yang telah dilakukan meliputi menjaga kebersihan individu maupun keluarga, terutama kebersihan makanan dan minuman serta lingkungan tempat tinggal. Disimpulkan bahwa penyebab penyakit diare pada siswa sekolah dasar karena kurangnya kesadaran hidup bersih dan sehat. Lebih lanjut, perlu ditingkatkan sosialisasi dan penyuluhan kesehatan oleh keluarga, sekolah, dan pihak terkait untuk lebih menyadarkan siswa tentang pola hidup bersih dan sehat .Â